“Entre Jesus, Apolo e Obatalá”: o hibridismo transcontinental do Vale do amanhecer e as relações de poder. - Silva, Roberto Calabria Guimarães da (2024)
This research had as its object of study to analyze the power relations, which at an institutional level, ranging from the command of work to the national/international command of religion, at a spiritual level organizes the hierarchy between men and women, present in the Vale do Amanhecer, through the perception of mediums. In order to respond to the problem presented by the object, the following objective was formulated: to investigate the religious practices of the Vale do Amanhecer, based on the analysis of its history, associating it with the story of Tia Neiva and relating it to transcontinental hybridism. This analysis will have as categories of analysis the transcontinental hybridism and the power relations. The choice for transcontinental hybridism occurred because it was not possible, in our analysis, to dialogue with the syncretism category, since the pantheon of the Valley forms a mosaic with entities from various faiths and continents such as Candomblé, Umbanda, Christianity, Kardecism, religions of Ancient Greece and Egypt, Buddhism and ufology entities as elements of the book Exilados de Capela, involving spiritual entities from religions of four continents that were incorporated into the Vale do Amanhecer, working in order and synchrony, without the mirroring of the entities, as was imposed on religions of African origin, in which an Orixá represented a Saint, as a way for the enslaved to be able to worship their faith without being repressed by their masters. To collect the data, forms with specific questions about the topic were sent, and the responses were analyzed using a quantitative and qualitative approach, in which the percentages, individual analysis, and the combined responses made it possible to understand the mediums' view of how they observe the hierarchy, defined by power relations, in a hybrid and transcontinental community. This research also focused on analyzing the place that women occupy in the hierarchy of the Valley. The research showed that most women perceived a devaluation of the place occupied by the female public, which leads to a contradiction, since the religion was created by Tia Neiva, who after her death was elevated to one of the main spiritual entities of the Vale do Amanhecer. This study will contribute to a better understanding of the relationships that are established in the Valley, as well as give visibility to the religious and spiritual practices experienced in the Vale do Amanhecer. The thesis is based on the dialogue between the categories of hybridism, taking as a basis Cancline (1997), a genre in which Nunes's (1985) thinking fits into the issue of women's protagonism in the Valley, and finally, multiculturalism based on the concepts of Touraine (1997). The thesis proposes to describe the Vale do Amanhecer in its historical context and in its relations with the religions that hybridize with it, emphasizing Catholicism, Kardecism and Umbanda, which exert a strong influence, both in the rituals and in the mediums and patients who attend.